Unmanned Helicopter Type Aircraft for the Pesticides and Fertilizers Application - L. A. Marchenko; M. V. Myzin; I. V. Kuznetsov; T. V. Mochkova; A. Yu. Spiridonov (Сельскохозяйственные машины и технологии)
Digital agricultural production is based on robotic agricultural technologies for the use of pesticides and fertilizers using unmanned aerial systems, which are based on unmanned aerial vehicles for monitoring agricultural land, the pesticides application, fertilizers and other agrochemicals. (Research purpose) To develop an unmanned helicopter based aircraft for applying pesticides and fertilizers, and to substantiate its technological parameters. (Materials and methods) The authors used methodological recommendations on the use of chemicals in the precision farming system, regulatory and technical documentation for unmanned aircraft systems. (Results and discussion) The authors determined the unmanned aerial vehicle main flight technical and technological parameters for the implementation of the applying pesticides and fertilizers process. They established the dependences of its productivity on the norms of introducing working fluids of pesticides and fertilizers, the agricultural field length, and the approach distance to the field. (Conclusions) The authors developed a helicopter-type unmanned aerial vehicle of a coaxial design with a take-off mass of 280 kilograms and a payload of 50-80 kilograms, a rotor diameter of 5.3 meters, a constructive boom width with sprayers of 5 meters, a working flight height of 1-5 meters, a working speed of 40-60 kilometers per hour, the rate of working fluid of pesticides application 10-20 liters per hectare and nitrogen fertilizers 30-120 liters per hectare. They established rational values for the application rates of pesticides – 10-20 liters per hectare, the agricultural field length – at least 0.8 kilometers, ensuring maximum productivity in flight hour when processing the agricultural field. They showed that the flight distance minimizing from the runway to the field significantly increased the productivity of applying pesticides and fertilizers.